2018
DOI: 10.1002/cphc.201800468
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Complex with by‐product HCl and Release Chloride Ions to Dissolve Aramid

Abstract: Because of the strong hydrogen-bond interaction among macromolecular chains, the addition of chloride salts is generally needed to offer Cl ions for the dissolution of aromatic polyamides. In this paper, poly-(benzimidazole-terephthalamide) which complexed with by-product HCl during polymerization (PABI-HCl) was prepared and imidazole compound as cosolvent was added into dimethylacetamide (DMAc) to dissolve PABI-HCl. Due to stronger affinity to protons, imidazole compound could in-situ complex with HCl of PABI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Liu et al made a similar discovery in their work on the synthesis of the polyaramid poly-(benzimidazole-terephthalamide). [44][45] They found that the addition of imidazole or sodium acetate to scavenge in-situ the released HCl greatly increased the solubility of their polyaramids.…”
Section: In-situ Ionic Liquid Formationmentioning
confidence: 99%
“…Liu et al made a similar discovery in their work on the synthesis of the polyaramid poly-(benzimidazole-terephthalamide). [44][45] They found that the addition of imidazole or sodium acetate to scavenge in-situ the released HCl greatly increased the solubility of their polyaramids.…”
Section: In-situ Ionic Liquid Formationmentioning
confidence: 99%
“…Based on the nucleophilic behavior,i ti sc rucial to enhance the nucleophilicity of the benzimidazole moiety to achieveC À Nc oupling on graphene with highere fficiency.I nm ost cases, DMAc rather than DMSO, with addition of lithium chloride (LiCl;D MAc/LiCl for short altogether), is the commonly used solventt od issolve aromatic polyamide. [15] Therefore, it seems unsuitable to enhance the reaction efficiency by changingt he solvents. Alternatively,t he enhancement of nucleophilicity could be achieved by adding ab asic catalyst.…”
Section: Resultsmentioning
confidence: 99%
“…Para‐aramid fibers such as Kevlar or Twaron have been widely applied in fiber‐reinforced composites and engineering materials due to their excellent mechanical properties and heat‐resistance . However, chemically inert surface and low compressive strength of aramid are two major problems for its application in reinforcing materials .…”
Section: Introductionmentioning
confidence: 99%